2020
DOI: 10.1038/s41598-020-78090-y
|View full text |Cite|
|
Sign up to set email alerts
|

Linear infrastructure habitats increase landscape-scale diversity of plants but not of flower-visiting insects

Abstract: Habitats along linear infrastructure, such as roads and electrical transmission lines, can have high local biodiversity. To determine whether these habitats also contribute to landscape-scale biodiversity, we estimated species richness, evenness and phylogenetic diversity of plant, butterfly and bumblebee communities in 32 km2 landscapes with or without power line corridors, and with contrasting areas of road verges. Landscapes with power line corridors had on average six more plant species than landscapes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Previously, we found that the ϒ‐diversity of plants was higher in landscapes with power line corridors, possibly because the power line corridors add grassland habitat to the landscape (Dániel‐Ferreira et al, 2020). Here, we found that power line corridors in the landscape also had a positive effect on plant α‐diversity in each grassland type, but there was no such effect for either of the insect groups.…”
Section: Discussionmentioning
confidence: 90%
“…Previously, we found that the ϒ‐diversity of plants was higher in landscapes with power line corridors, possibly because the power line corridors add grassland habitat to the landscape (Dániel‐Ferreira et al, 2020). Here, we found that power line corridors in the landscape also had a positive effect on plant α‐diversity in each grassland type, but there was no such effect for either of the insect groups.…”
Section: Discussionmentioning
confidence: 90%
“…This could be partially due to an increase in bird detectability along roads. However, roads, tracks, and rails often have an ecotonal effect on the surrounding landscapes (Dániel-Ferreira et al 2020 ) and are lined with narrow strips of embankments or shrubbery, providing potential habitats for birds (Coffin 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the land use in non-protected areas already benefit early-successional habitats and species. For example, forest clear-cuts, road verges, and extensively managed green spaces can provide habitat suitable for disturbance-dependent species (Öckinger et al 2009 ; Rubene et al 2014 ; Dániel-Ferreira et al 2020 ). Thus, implementation of disturbances under a land sharing strategy can result in smaller changes that does not compete with other conservation goals (Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, protected areas are few, and may be too small for natural disturbance dynamics to operate adequately (Baker 1992 ; Brackhane et al 2021 ). In contrast, production landscapes typically contain a large proportion of early-successional habitats, and management practices that might emulate natural disturbances (Rubene et al 2014 ; Batáry et al 2015 ; Dániel-Ferreira et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%